PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTs ALKHAIRAAT TONDO DALAM MENYELESAIKAN SOAL CERITA HIMPUNAN DITINJAU DARI SELF-EFFICACY: Profile of Mathematical Communication Ability of MTs Alkhairaat Tondo Students in Solving Set Story Problems Based on Self-Efficacy - Hidayah, Nur; Paloloang, Baharuddin; Pathuddin, Pathuddin; Hasbi, Muh. (Universitas Tadulako, 2024)
This study aims to obtain the profile of mathematical communication ability of MTs Alkhairaat Tondo students in solving set story problems based on self-efficacy. This type of research was descriptive qualitative approach. The subjects of this study consisted of 2 students selected from the 22 students in class VIIB of MTs Alkhairaat Tondo who had completed a self-efficacy questionnaire, one student with high self-efficacy and one with low self-efficacy. The results of this study are as follows: (1) The subject with high self-efficacy achieved all three indicators, namely being able to express mathematical ideas verbally and in writing; using mathematical terms, symbols, and structures to model mathematical situations or problems; and understanding, interpreting, and evaluating mathematical ideas both orally and in writing. (2) The subject with low self-efficacy did not achieve all three indicators of mathematical communication skills.